Analisis User Throughput Based Mobility Load Balancing Menggunakan Prediksi Regresi Logaritmik Reference Signal Received Quality Di Jaringan Akses Radio Long Term Evolution - Achmad Rizal Danisya; Rendy Munadi; Sofia Naning Hertiana (JURNAL INFOTEL, 2018)
The improvement of Long Term Evolution (LTE) radio access network services is affecting the increased value of traffic load in its network, which is causing traffic unbalance between cells in LTE Radio Access Network (RAN). Users will be served with ineffective resource block allocation which will make the total of gained throughput are not optimal. A method is required to move network load from overloaded cells to underloaded cells in order to balance the resource block allocation optimally. By using NS-3.26 simulation, User Throughput Based (UTB) predictive Mobility Load Balancing (MLB) method is tested with RandomWalkMobilityModel for each user. This method produces an improvement of 2,29 % in average of total throughput of 63,33 % successful optimization.